2010
DOI: 10.1097/cji.0b013e3181c0c1cb
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Interleukin-21 Increases Antitumor Immunity, Tumor-infiltrating CD8+ T-cell Density and Activity, and Enlarges Draining Lymph Nodes

Abstract: Interleukin (IL)-21 is a novel cytokine in clinical development for the treatment of cancer. In this study, we have compared the efficacy of subcutaneous and intratumoral (IT) administration of IL-21 protein in two syngeneic mouse tumor models, RenCa renal cell carcinoma and B16 melanoma, and investigated the mechanisms by which IL-21 enhances CD8 T-cell-mediated antitumor immunity. We found that in comparison to subcutaneous administration, IT administration of IL-21 more potently inhibited tumor growth and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…I.t. administration of IL-21 showed better treatment effect than subcutaneous injection and caused superior CD8 T cell proliferation [89]. I.t.…”
Section: It Immunotherapy With Cytokinesmentioning
confidence: 99%
“…I.t. administration of IL-21 showed better treatment effect than subcutaneous injection and caused superior CD8 T cell proliferation [89]. I.t.…”
Section: It Immunotherapy With Cytokinesmentioning
confidence: 99%
“…However, because of the fact that IL-21 possesses extensive immunomodulating effects, it has recently attracted attention as a tool to generate anti-tumor responses for cancer immunotherapy (di Carlo et al 2007;Sondergaard and Skak 2009;Spolski and Leonard 2008). Several reports demonstrated that administration of recombinant IL-21 (Frederiksen et al 2008;Moroz et al 2004;Sondergaard et al 2010Sondergaard et al , 2007, IL-21 gene expression vectors (Brady et al 2004;Kishida et al 2003;Wang et al 2003), or IL-21 gene-modified cells (Croce et al 2008;Dou et al 2009;Fang et al 2008;Furukawa et al 2006;Kumano et al 2007;Ugai et al 2003a,b;Zhao et al 2010) elicits significant anti-tumor responses. In addition, IL-21 also has the ability to inhibit tumor angiogenesis (Castermans et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…21 In syngeneic mouse models of melanoma and renal cell carcinoma, IL-21 administered intratumorally was able to strongly inhibit tumor growth and increase the frequency of tumor-infiltrating CD8 C T cells. 42 In addition, delivery of IL-21 showed low toxicity and did not induce vascular-leak syndrome, a dose-limiting toxicity associated with other clinically utilized cytokines, such as IL-2. 43 IL-21 antitumor activities have been exploited in association with several other molecules, which showed either additive or synergistic effects.…”
Section: Discussionmentioning
confidence: 99%